An underwater robot with self-adaption mechanism for cleaning steel pipes with variable diameters. Issue 2 (25th January 2018) - Fan, Jinchang; Yang, Canjun; Chen, Yanhu; Wang, Hansong; Huang, Zhengming; Shou, Zhicheng; Jiang, Ping; Wei, Qianxiao
Abstract : Purpose: This paper aims to present an underwater climbing robot for wiping off marine life from steel pipes (e.g. jackets of oil platforms). The self-adaption mechanism that consists of a passive roll joint and combined magnet adhesion units provides the robot with better mobility and stability. Design/methodology/approach: Adhesion requirements are achieved by analyses of falling and slipping. The movement status on pipes is analyzed to design the passive roll joint. The optimized structure parameters of the combined magnet adhesion unit are achieved by simulations. An approximation method is established to simplify the simulations conditions, and the simulations are conducted in two steps to save time effectively. Findings: The self-adaption mechanism has expected performance that the robot can travel on pipes in different directions with high mobility. Meanwhile, the robot can clean continuous region of underwater pipes' surface of offshore platforms. Practical implications: The proposed underwater robot is needed by offshore oil platforms as their jackets require to be cleaned periodically. Compared with traditional maintenance by divers, it is more efficient, economic and safety. Originality/value: Due to the specific self-adaption mechanism, the robot has good mobility and stability in any directions on pipes with different diameters. The good performance of striping attachments from pipes makes the underwater robot be a novel solution to clean steel pipes.